Functional - cognitive abbreviation - Babanov Bakhadir Abdikadirovich (Genius Journals, 2022)
Not all new information encountered on a topic has an understandable reference system. In many cases there will be information gaps or lack of context. There, schemes play a hidden role by finding relationships between different ideas or concepts. This article is a cognitive acronym, what is it? provides information on how it is composed and structured.
Keywords: Cognitive functioning; cognitive abbreviation; psychosocial presentation; clinical psychology